Pengaruh Wacana Gender Dalam Pembangunan Hukum Keluarga di Indonesia - Asep Syarifuddin Hidayat (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2013)
The Effect of Gender Discourse in the Development Family Law in Indonesia. One of the social movements that emerged and gained its strength in the second half of the 20th century is feminism movement that encourages a structural change in the patriarchal structure society and equality between men and women. The movement also includes Muslim countries. The struggle of feminism or gender equality gained its momentum when the practice of discrimination towards women prevail in the Muslim community that is supported by treasury classical Islamic law (fiqh). It is on that particular context, the process of family law reform in Muslim countries at the end of the century-20s became an important arena of women's advocacy groups of their rights, as well as incorporate aspects of family law reform. DOI: 10.15408/jch.v1i1.2985